Infant Intersubjectivity: Research, Theory, and Clinical Applications - Trevarthen, Colwyn; Aitken, Kenneth J. (Journal of child psychology and psychiatry, 2001)
We review research evidence on the emergence and development of active “ self‐and‐other ” awareness in infancy, and examine the importance of its motives and emotions to mental health practice with children. This relates to how communication begins and develops in infancy, how it influences the individual subject's movement, perception, and learning, and how the infant's biologically grounded self‐regulation of internal state and self‐conscious purposefulness is sustained through active engagement with sympathetic others. Mutual selfother‐ consciousness is found to play the lead role in developing a child's cooperative intelligence for cultural learning and language. A variety of preconceptions have animated rival research traditions investigating infant communication and cognition. We distinguish the concept of “ intersubjectivity ”, and outline the history of its use in developmental research. The transforming body and brain of ahumanindividual grows in active engagement with an environment of human factors‐organic at first, then psychological or inter‐mental. Adaptive, human‐responsive processes are generated first by interneuronal activity within the developing brain as formation of the human embryo is regulated in a support‐system of maternal tissues. Neural structures are further elaborated with the benefit of intra‐uterine stimuli in the foetus, then supported in the rapidly growing forebrain and cerebellum of the young child by experience of the intuitive responses of parents and other human companions. We focus particularly on intrinsic patterns and processes in pre‐natal and post‐natal brain maturation that anticipate psychosocial support in infancy. The operation of an intrinsic motive formation (IMF) that developed in the core of the brain before birth is evident in the tightly integrated intermodal sensory‐motor coordination of a newborn infant's orienting to stimuli and preferential learning of human signals, by the temporal coherence and intrinsic rhythms of infant behaviour, especially in communication, and neonates' extraordinary capacities for reactive and evocative imitation. The correct functioning of this integrated neural motivating system is found to be essential to the development of both the infant's purposeful consciousness and his or her ability to cooperate with other persons' actions and interests, and to learn from them. The relevance of infants' inherent intersubjectivity to major child mental health issues is highlighted by examining selected areas of clinical concern. We review recent findings on postnatal depression, prematurity, autism, ADHD, specific language impairments, and central auditory processing deficits, and comment on the effcacy of interventions that aim to support intrinsic motives for intersubjective communication when these are not developing normally.